2019
DOI: 10.3390/antib8010025
|View full text |Cite
|
Sign up to set email alerts
|

Human Domain Antibodies to Conserved Epitopes on HER2 Potently Inhibit Growth of HER2-Overexpressing Human Breast Cancer Cells In Vitro

Abstract: The FDA approval of two anti-HER2 monoclonal antibodies, trastuzumab and pertuzumab, and an antibody-drug conjugate, trastuzumab emtansine, has transformed clinical practice for HER2-positive cancers. However, not all patients respond to therapy, and the majority of responders eventually develop resistance. In addition, cardiotoxicity is a major safety concern for their clinical use. Thus, there remains a need for the discovery and development of novel classes of HER2-targeted therapeutics with high efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Anti-HER2 antibodies have improved clinical treatment effects for metastatic CRC patients. 43 So far, the Food and Drug Administration has approved two anti-EGFR drugs cetuximab and panitumumab for the treatment of colorectal cancer, so EGFR can be used as an important and clinically relevant therapeutic target for colon cancer. However, the duration of response to anti-HER2 antibodies lasts short.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HER2 antibodies have improved clinical treatment effects for metastatic CRC patients. 43 So far, the Food and Drug Administration has approved two anti-EGFR drugs cetuximab and panitumumab for the treatment of colorectal cancer, so EGFR can be used as an important and clinically relevant therapeutic target for colon cancer. However, the duration of response to anti-HER2 antibodies lasts short.…”
Section: Discussionmentioning
confidence: 99%
“…Third, because human sdAb is small, it can access a hidden epitope that is not accessible to the large-size conventional mAb [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has good tissue and tumor penetration [19]. It can access an epitope inaccessible to the large-size conventional mAb [20,21]. Moreover, human sdAb can be easily manufactured in bacteria at a very low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, HER2 protein is expressed only in the fetal period, and in a few tissues at a low level or not expressed in adulthood, but it is overexpressed in many tumor tissues. It has been confirmed that 12–35% of gastric cancers have HER2 overexpression, and HER2 is an independent prognostic factor of gastric cancer [ 21 ]. The results of Roy et al [ 22 ] showed that HER2 protein expression in patients with gastric cancer combined with lymph node metastasis was significantly higher than that in those without lymph node metastasis; HER2 protein expression in patients with infiltration reaching beyond the serosa was significantly higher than in those with infiltration within the serosa, and HER2 protein in lymph node metastasis of gastric cancer was highly expressed.…”
Section: Discussionmentioning
confidence: 99%